A comprehensive genome‐wide analysis of long noncoding RNA expression profile in hepatocellular carcinoma. (18th October 2017) - Cui, Hongxia; Zhang, Yunxing; Zhang, Qiujie; Chen, Wenming; Zhao, Haibo; Liang, Jun
Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignancies worldwide, especially in East Asia and China. Long noncoding RNAs (lncRNAs) are emerging as critical regulators that may be involved in the development and progression of cancers in humans. However, the contributions of lncRNAs to HCC development, metastasis, and recurrence remain largely unknown. In this study, we comprehensively investigated lncRNA expression profile in HCC and normal tissues using TCGA RNA sequencing data, one RNA sequencing dataset, and two microarray datasets from GEO. By analyzing these four datasets, we identified hundreds of expression‐dysregulated lncRNAs in HCC tissues compared with normal tissues. Genomic copy number variation analysis showed that many of those lncRNAs disorder are related to the copy number amplification or deletion. Moreover, several lncRNAs expression levels are associated with HCC patients' overall and recurrence‐free survival, such as RP1‐228H13.5, TMCC1‐AS1, LINC00205, and RP11‐307C12.11. Furthermore, we identified two lncRNAs termed PVT1 and SNHG7 that may be involved in HCC cells metastasis by comparing lncRNAs expression profiles between early recurrence HCC tissues with metastasis and late recurrence HCC tissues without metastasis. Finally, loss‐of‐function assays confirmed that knockdown of SNHG7 and PVT1 impaired HCC cells invasion. Taken together, these findings may provide a valuable resource for further identification of novel biomarkers and therapeutic targets for HCC patients. Abstract : lncRNAs are emerging as critical regulators that are involved in the development and progression of cancers in humans. We comprehensively investigated lncRNA expression profiling in HCC and normal tissues; these findings may provide a valuable resource to further identify novel biomarkers and therapeutic targets of HCC.